Release of aroma components from agarose gels during human chewing: Effects of agarose molecular weight and chewing cycles. (May 2023) - Moritaka, Hatsue; Itazu, Ayako; Okamura, Yoshiyuki; Fuwa, Masako; Ishihara, Miki; Nishinari, Katsuyoshi
Abstract: Experiments were conducted using a method of collecting aroma compounds in the mouth through one nostril. Three types of agarose gels with different molecular weights and nine types of aroma compounds were used as samples. After the agarose gel was chewed 0–30 times while holding breath, aroma compounds were collected by blowing intraoral air into the sampling bag through the nostril. The effects of the number of chewing cycles and the type of agarose gel on the release rate of aroma compounds were investigated using relative release values, Qc / Q0 (where Qc is the amount of aroma compounds collected after chewing and Q0 is the amount collected without chewing). The relative release value increased with increasing number of chewing cycles, and the degree of increase in the relative value depended on the molecular weight of agarose. The relative release values for low chewing cycles were similar for all types of gels. At higher chewing cycles, the relative release value increased in gels with lower network densities than in other types of gels. It was suggested that the molecular weight of agarose and the number of chewing cycles changed the mechanism of flavor release. Graphical abstract: Image 1 Highlights: Aroma compounds released in vivo were examined by relative release values. Amount of aroma release changed with chewing and gel structure. Mechanism of aroma release is considered to change accordingly.